Pemetaan Tren Penelitian Manajemen Krisis: Analisis Bibliometrik dengan VOSviewer - Iswardhani, Indri (PT. Alahyan Publisher Sukabumi, 2025)
This study examines the trends and primary research focuses in the field of crisis management using bibliometric methods supported by VOSviewer software. The analysis was conducted on 493 scholarly articles retrieved from Google Scholar with the keyword